Evaluation of standard reagents for radial-immunodiffusion assays. In vitro control of rabies vaccines - MICELI Graciela S. (Revista do Instituto de Medicina Tropical de São Paulo, 2000)
The RID assay is one of the in vitro methods used for in-process control in the production of rabies vaccines for veterinary use. It has been shown to be very useful for determining antigen concentration in the final bulk product. The work presented in this paper, including the production and standardization of candidate standard reagents for use in the Radial Immunodiffusion Assay (RID) was carried out at the Pan American Institute for Food Protection and Zoonoses (INPPAZ/PAHO/WHO). The study was completed with the cooperation of the Faculty of Veterinary Sciences, National University of La Plata (NULP), Argentina, where the validation of the proposed standards and the quality control of samples from 28 different batches of rabies vaccines produced with Pasteur strain rabies virus (PV) in BHK cells were performed. The activity of the vaccines was determined by in vivo (NIH) and in vitro (RID)assays. The results of the candidate reagents for the reagent standardization tests showed stability, sensitivity and reproducibility. The Relative Potency the 1.2 between the problem vaccines and the reference vaccine was estimated by variance and regression analysis. The results of our validation study show that the INPPAZ (PAHO/WHO) is capable of producing and distributing the above-mentioned standard reagents, as well as of providing support for the incorporation of the RID technique (sensitive, rapid and inexpensive) to the laboratories that manufacture rabies vaccines in Latin America and the Caribbean.